2020
DOI: 10.1021/acsami.0c04897
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Detection of Endotoxin in Bacteriostatic Process by SERS Chip Integrated Array Microchambers within Bioscaffold Nanostructures and SERS Tags

Abstract: In order to achieve real-time and in situ detection of endotoxin, which is an important and significant clinical test index, surface-enhanced Raman spectroscopy (SERS) chip integrated array microchambers within bioscaffold nanostructures and a SERS monitoring strategy were proposed in this paper. After sputtering of nanogold on the cicada wing, which was selected as a natural template, and polydimethylsiloxane bonding, array-type chambers within bioscaffold nanostructures were prepared for in situ bacterial cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 27 publications
(41 reference statements)
0
34
0
Order By: Relevance
“…However, the SERS system detects the signal from the few NPs available in the laser area -that is about 1000 AuNPsproviding a real LOD of 160 (± 10) fg/mL, that is lower than the detection limit of LAL assays (13). Furthermore, the proposed SERS approach does not suffer the limit of the fluorophore quenching, which is a serious issue in colorimetric and fluorogenic LPS detection assays, especially for nanoparticles, and allows to measure the number of LPS molecules directly on the single AuNP, without the use of SERS tag or functionalization procedures, as previously reported (21). Indeed, since the number of LPS molecules adsorbed on the NPs, in saturation condition, can be evaluated by the DLS measurements, as reported in the Supplementary Table 1, it is possible to estimate the SERS SNR as a function of the number of LPS molecules per AuNP (47).…”
Section: Sers Measurements Of Lps-aunps and Limit Of Detectionmentioning
confidence: 68%
See 2 more Smart Citations
“…However, the SERS system detects the signal from the few NPs available in the laser area -that is about 1000 AuNPsproviding a real LOD of 160 (± 10) fg/mL, that is lower than the detection limit of LAL assays (13). Furthermore, the proposed SERS approach does not suffer the limit of the fluorophore quenching, which is a serious issue in colorimetric and fluorogenic LPS detection assays, especially for nanoparticles, and allows to measure the number of LPS molecules directly on the single AuNP, without the use of SERS tag or functionalization procedures, as previously reported (21). Indeed, since the number of LPS molecules adsorbed on the NPs, in saturation condition, can be evaluated by the DLS measurements, as reported in the Supplementary Table 1, it is possible to estimate the SERS SNR as a function of the number of LPS molecules per AuNP (47).…”
Section: Sers Measurements Of Lps-aunps and Limit Of Detectionmentioning
confidence: 68%
“…Therefore, the AuNPs allows direct sensing of LPS, providing a good enhancement and reproducibility of the signal and avoiding the use of Raman reporters as previously reported (21). At the same time, the proposed approach allows for noninvasive and non-destructive characterization of the local chemical structure of the molecules attached to the AuNPs, avoiding the use of functionalization procedures.…”
Section: Raman and Sers Characterization Of Lps Molecules On Aunpsmentioning
confidence: 83%
See 1 more Smart Citation
“…The outcomes received with the aid of using SERS evaluation have been steady with the ones of the ELISA kit. 130 An innovative work describes the use of SERS for the label-free quantitative nanoscale identification of the LPS adsorbed on the surface of 50 nm AuNPs. This SERS method was an efficient tool to detect LPS on the AuNP surface and the basis for the development of a novel specific and sensitive LPS-detection sensor based on the use of SERS and AuNPs.…”
Section: Biosensors; Modern Methods For the Recognition Of Lpsmentioning
confidence: 99%
“…Recent ultra-sensitive SERS-based methods can detect single molecule reactions on a substrate surface [12,13]; however, Raman-based studies on the unique spectra of bacterial endotoxin are currently very limited. A recent study reported the in situ detection of a Pseudomonas aeruginosa endotoxin using a nanogoldsputtered cicada wing as a SERS chip; however, it used 4-mercaptobenzoic acid (4-MBA) and p-aminophenol (PAP) as SERS reporters rather than the intrinsic SERS spectra of the endotoxin itself [14]. In order to establish a highly sensitive SERS platform for intrinsic endotoxin detection, highly reproducible and practical substrates are essential.…”
Section: Introductionmentioning
confidence: 99%